Exploring the Influence of Student-Athlete Advisory Committee Participation on Leadership and Post-Graduate Career Development - Heim, P.; Stokowski, S.; Springer, Daniel S.; Rubin, Lisa M.; Miller, M.T. (My University, 2022)
The Student-Athlete Advisory Committee (SAAC) is comprised of student-athletes that provide insight on their experiences, influencing policies that affect rules and regulations at the institutional, conference, and national level(s). SAAC participation allows student-athletes to transfer the skills learned on the playing field into a professional setting. These skills are a foundational component for athletes’ character and moral development. Despite the proliferation of SAACs across the NCAA membership institutions, there is a dearth of empirical studies examining these committees and the outcomes they achieve. The purpose of this study is to explore the influence of SAAC participation on post-graduate career development. Using a phenomenological approach to research, semi-structured interviews and observations were conducted with eight former SAAC student-athletes to discover the impacts of their SAAC experience. Throughout the data, two major themes appeared, career preparation and future leadership preparation. Ultimately, the participants indicated that participating in SAAC translated into various leadership skills, helping this population prepare for post-graduation endeavors, and explore their self-concept beyond the athletic realm.